Strategies for a more sustainable path toward Singapore's food production goals - Koh, Deborah (2024)
Plans to boost Singapore’s local food production have been hindered by global disruptions, leading to a wave of local farm closures in their aftermath. On the home front, reorienting existing strategies could help address demand- and supply-related gaps. Opportunities for grant realignment, public messaging, and education may provide a means to ease business continuity challenges and help faltering consumer demand gain traction over time.